The Study of Traditional Foods, Ornaments, Costumes and Housing Patterns of the People of Ravi River Basin in Himachal Pradesh, India - Nikesh Sharma (PT FORMOSA CENDEKIA GLOBAL, 2022)
In Bharmour tehsil, Cheena and inferior types of millets are used. Previously, the diet of Gaddis was simple and did not permit them much variation. In winter season all the people of this basin wear woolen garments but in summer season they wear cotton garments. As would be expected, with the process of modernization, a change took place in the traditional dress (Punjab castes, 1916). Every region has wear jewellery that is typical and peculiar to it. Jewellery and ornaments were fashioned by goldsmiths (suniars) all over Ravi River basin in Himachal Pradesh (C.S. Panchani). The houses are generally two to three storeyed buildings with separate kitchen and cowshed and the design of the houses is not uniform but its design depends upon the location of site. In a mountainous area like Bharmour, the village is not laid out in a systematic way and a number of factors seem to have determined the pattern of settlement. The permanent villages of the Gaddis on an average lie between an altitudes of 7000 to 10000 feet above sea level and they are small sized villages ranging from 30 to 200 families. The inhabitants of most of these villages are exclusively the Gaddis (Punjab State Gazetteer, 1904).